2010
DOI: 10.1007/s11606-010-1542-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine and Self-Rated Health Status: Results from a National Survey

Abstract: BACKGROUND: Despite the absence of conclusive evidence of effectiveness, complementary and alternative medicine (CAM) is used by 4 of 10 adults in the US; little is known about the association between CAM use and health status. OBJECTIVE: To determine the relation between CAM use and self-reported health status and health improvement over time. DESIGN AND PARTICIPANTS:We performed a secondary database analysis using data from the 2007 National Health Interview Survey of non-institutionalized US residents condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 66 publications
6
44
2
5
Order By: Relevance
“…9,31 Slightly more females than males used CAM but the difference was not statistically significant in our study, though similar statistically-significant results have been shown in other studies. 9,31,32 National surveys indicate CAM use is greater in younger than older ages, 32 but several studies have shown the use to be quite prevalent in older adults as well. 10,33-35 …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…9,31 Slightly more females than males used CAM but the difference was not statistically significant in our study, though similar statistically-significant results have been shown in other studies. 9,31,32 National surveys indicate CAM use is greater in younger than older ages, 32 but several studies have shown the use to be quite prevalent in older adults as well. 10,33-35 …”
Section: Discussionsupporting
confidence: 79%
“…Combined with increased awareness, changing health practices, fear of addiction to conventional medications, and possible dissatisfaction with conventional care, 5-7 the prevalence of CAM has been increasing for decades both worldwide 8 and in the United States, specifically, 9 with a substantial 8.3% increase in usage from 1990 to 1997, 10 and only a modest drop between 2002 and 2007. 11 The drop could have been a result of the St. John’s Wort studies that emerged during that time period and several reports of toxicity of certain agents, all inciting some element of fear.…”
mentioning
confidence: 99%
“…In the USA, the use of CAM rose from 33.8 to 42.1 % from 1990 to 1997 among the total population [1], while in the 2000s this ratio was 34–37 % [2, 3]. A recent systematic review of surveys in the UK indicated, 51.8 % of the population applied alternative remedies at least once during their lifetime [4].…”
Section: Introductionmentioning
confidence: 99%
“…Az elmúlt évtizedekben világszerte számos felmérés azt mutatta, hogy nagy az érdeklődés a nem konvencionális módsze-rek iránt [1]. Az Egyesült Államokban 1990-1997 kö-zött 33,8%-ról 42,1%-ra nőtt a komplementer és alternatív gyógymódok (CAM) alkalmazása a teljes népesség körében [2], míg az ezredforduló utáni évtizedben a felnőtt lakosság 34-37%-a vett igénybe ilyen gyógymó-dokat [3,4]. Európában a statisztikák alapján az 1990-es években a lakosság 20-50%-a vett igénybe természet-gyógyászati kezelést [5].…”
unclassified